ANALISIS TINGKAT KESEHATAN PT. BANK PERKREDITAN RAKYAT BINTANG MITRA PERIODE 2011-2013 DENGAN ANALISIS CAMEL - Meilina, Anie Sasmita; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Banking management performance is very important in banking activities. Banking activity is theintermediation institution or the financial intermediary between the funding owner group and thegroup who needs fund. The purpose of this research is to conduct analysis to the banking healthy levelon PT Bank Perkreditan Rakyat Bintang Mitra in Surabaya, for 2011-2013 periods. The assessmentanalysis of banking healthy level has been carried out by using CAMEL method (Capital, Asset,Management, Earning, and Liquidity) which is based on the decree of BI director No.30/12/KEP/DIRon April 30th, 1997. The result of the research shows that the bank healthy level of PT BPR BintangMitra in 2011-2013 was categorized healthy with consecutive score was 96.9 in 2011, 97.9 in 2012,and 98.5 in 2013. But from the component of Capital Adequacy Ratio (CAR) in 2012 it increasedsignificantly, it was influenced by the decreased of provided credit and the increased of interbankassets account with the number of capital that is relatively unchanged. So the managed fund which ismanaged fund is less productive, and the Loan to Deposit Ratio is required to be improved since itsratio is still under the fund that is collected in the liquid obligation.Keywords: Banking Healthy Level Analysis, CAMEL Analysis, Rural Bank (Bank PerkreditanRakyat).